Study and Analysis of Power MOSFET Characteristics in Radiation Environment - KHALID, HESHAM (Universiti Teknologi PETRONAS, 2016)
Semiconductor devices are playing a vital role in the industry of integrated circuits and solid state devices because of their fast switching speeds and low power consumption capabilities. Effects of radiations in space can cause changes in the electrical characteristics causing threshold voltage shifts and drain current degradation. Damaging mechanisms such as Displacement Damage, Single Event Effects (SEE), Total Ionization Dose (TID) effects are sole reason of these effects.